2021
DOI: 10.1155/2021/6641072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Influencing Factors on the Deformation of Sheet Pile Wall with a Relieving Platform

Abstract: Owing to the complexity of the sheet pile wall with a relieving platform, there are a large number of factors that affect the mechanical and deformation characteristics of the wall structure. Moreover, studying the influencing factors on the deformation of the retaining wall is beneficial in the selection of design parameters and deformation control. 28 groups of test models of the retaining wall structure are designed to analyze the effect on the deformation of rib pillars and determine the reasonable width a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Existing research on retaining walls with relief shelves mainly includes model tests [5][6][7][8][9][10][11] and numerical analysis [12][13][14][15], involving the cantilever retaining wall with relief shelves [5][6][7][8][11][12][13][14][15]and the sheet pile wall with relieving platforms [9][10]. Qualitative studies with model tests revealed that relief shelves could effectively reduce the lateral earth pressure acting on the retaining wall [5], and could effectively reduce the horizontal displacement of the retaining wall [10]. Longer relief shelves resulted in a more obvious unloading effect [8], and the lateral earth pressure under the relief shelf followed a certain distribution law [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on retaining walls with relief shelves mainly includes model tests [5][6][7][8][9][10][11] and numerical analysis [12][13][14][15], involving the cantilever retaining wall with relief shelves [5][6][7][8][11][12][13][14][15]and the sheet pile wall with relieving platforms [9][10]. Qualitative studies with model tests revealed that relief shelves could effectively reduce the lateral earth pressure acting on the retaining wall [5], and could effectively reduce the horizontal displacement of the retaining wall [10]. Longer relief shelves resulted in a more obvious unloading effect [8], and the lateral earth pressure under the relief shelf followed a certain distribution law [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the flexural strength of steel sheet piles on the basis of U-shaped steel sheet pile retaining wall construction. During design, the strength and stiffness were reduced to the expected full composite values, and RMA was shown to be effective for sheet piles 5,6 . Some scholars also introduced a method of using large-diameter steel sheet pile cofferdams with reinforced concrete supporting ring beams.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used RWs include the gravity RWs [1,2], which rely on the balance between the self-weight of the RW and the earth pressure to maintain the stability of the wall and have disadvantages including long construction periods and poor greening function; gabion RWs [3,4], which are flexible gravity retaining structures formed by stacking gabion cages containing various grades of stone in an orderly manner; reinforced earth RWs [5,6], which are formed by adding steel bars in the soil to stabilize the soil by the friction between the steel bars and the soil, but their construction quality is greatly affected by the construction site factors and slope surfaces are required to be gentle; cantilever/counterfort RWs [7,8], which maintain stability by the weight of the fill on the bottom plate but have the disadvantages of complex construction technology, long construction periods, and excessive corrosion of drain pipes; and sheet pile walls [9][10][11], which uses baffles to block the soil between the deeply buried piles and they have similar disadvantages to those of the cantilever/counterfort RWs.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the safety coefficient and soil/wall friction significantly affect the relative conservativeness of these design methods. Based on model tests, Ming et al [10] discussed the factors affecting the deformation of sheet pile walls with pressure relief platforms and provided suggestions for the rational values of sheet width and buried depth. Taku et al [11] performed a 2D FEA of cantilever sheet pile walls using the ABAQUS software.…”
Section: Introductionmentioning
confidence: 99%